The Hebrew Goddess Asherah in the Greek Septuagint - Worthington, Richard (Feminist theology, 2018)
When reading the Hebrew Bible, it is clear that the goddess Asherah is given a negative image. There are some fascinating probable misreadings, including one showing that she once might have had a more exalted role: in Deuteronomy 33:2 at the Lord's right hand there was a 'fiery law', or was it 'Asherah'? However, it appears that the Greek Septuagint preserves some additional references to Asherah which are surprisingly positive. In some of the places examined Asherah can confidently be assumed to be underneath the Greek word for 'grove' (the traditional rendering of 'Asherah'). Additionally, there are places where Asherah does not occur but the Greek translation gives us evidence that the word Asherah was there originally. Finally, two 'goddess passages' (Ezekiel 8 and Jeremiah 44) are shown to have significantly different emphases regarding Asherah when read in the Greek or other ancient translations.